Profile of Patients with Seizure Disorders in Adults Presenting to Manipal Teaching Hospital - jwarchan, Bishnu; Dhungana, Durga; Dhakal, Anil; Acharya, Ramesh Raj; Yogi, Nikunja (Journal of College of Medical Sciences-Nepal, 2024)
Background Seizures can affect people of all ages, including adults. Symptoms of seizures can vary widely, including muscle convulsions, loss of consciousness, staring spells, confusion, repetitive movements, and sensory disturbances. Seizures can be caused by various factors, such as epilepsy, head injuries, brain infections, stroke, and other medical conditions. Diagnosis typically involves a thorough medical history, neurological examination, and sometimes ancillary tests. Treatment options depend on the underlying cause. Methods This was a prospective cross‑sectional hospital‑based study conducted on 63 cases presenting with adult onset seizures. Details of the patients of the age of 18 years and above were included and entered as per the structured performa. Statistical analysis was done by SPSS in terms of frequency and percentage. Results The mean age was with 46.84 years with male gender predominance. Adult onset seizures were most prevalent in the middle‑aged adults than elderly; generalized seizures were more common than focal seizures. Most common neuroimaging finding was infarct followed by neurocysticercosis and intracranial bleed. Conclusions Identification and awareness about the possible etiological factors and seizure type help in better management of seizure patients.